On Writing Mathematical Papers in English - Yessenbayeva, G.A.; Makazhanova, T.Kh. (Publ.KarSU, 2017)
The article is intended to provide practical help for authors of mathematical papers. It is written mainly for non-English speaking writers but should prove useful even to native speakers of English who are beginning their mathematical writing and may not yet have developed a template of the structure of mathematical discourse. The article is oriented mainly to research mathematics but applies to almost all mathematics writing, except more elementary texts. There is no intention whatsoever to impose any uniformity of mathematical style. Quite the contrary, the aim is to encourage prospective authors to write structurally correct manuscripts as expressively and flexibly as possible, but without compromising certain basic and universal rules.
Ағылшын тілінде математикалық мəтіндердің жазылуы туралы
О написании математических текстов на английском языке
Keywords: language of mathematics; advice and rules on writing mathematical texts